Training of the future officers for educational work with staff in higher education (Pedagogy of Higher and Secondary Education, 2014)
Ischenko S. A. Training of the future officers for educational work with staff in higher education.This paper examines the essence of the concept of «readiness future officers to educational work», the basic ingredients ready, set specific knowledge and skills that should have future officers fo the effective performance of their professional activities.
Keywords: readiness; future officer; education; professional activity